Design and performance of high-toughness ultra-thin friction course in south China. (20th June 2020) - Yu, Jiangmiao; Chen, Fuda; Deng, Wen; Ma, Yimin; Yu, Huayang
Highlights: A novel design of ultra-thin asphalt layer is proposed. The high-toughness ultra-thin friction course provides excellent engineering performance. The "functional design" of asphalt surface layer is feasible. Abstract: Ultra-thin asphalt overlay has been widely applied in both new pavement construction and road maintenance. It brings better driving comfort by providing superior skid resistance and lower traffic noise. However, in most cases the functional performance is not durable under repeated vehicle loading and abrasion. By simultaneously optimizing the material properties, gradation design and construction technology, this study proposed a novel design of ultra-thin asphalt overlay named "High-toughness Ultra-thin Friction Course (HUFC)". The gradation design is based on the improved CAVF (Coarse Aggregate Voids Filling) method. The nominal maximum size of aggregate of HUFC is 8 mm, and the layer thickness is 1.0–1.5 cm. HUFC-8 uses high-viscosity and high-elasticity asphalt binder as bonding material for aggregates, and high-viscosity emulsified asphalt to bond with lower layers. A series of laboratory and field tests were performed to evaluate the mechanical and functional performance of HUFC-8. Laboratory test results showed that HUFC-8 exhibited excellent and durable skid resistance and noise reduction function. Moreover, the enhancement from the interlocking effect of the coarse aggregate and the increase of the asphalt film made HUFC-8 more durable to fatigue cracking. Based on field performance evaluation, HUFC-8 had strong bonding to lower pavement layer and exhibited good performance on flatness restoration when the low layer is not smooth. The HUFC layer has been successfully applied in over 100 field projects in south China since 2017. The excellent field performance makes it a promising paving technology for larger-scale applications.